2020
DOI: 10.1016/j.intimp.2020.106314
|View full text |Cite
|
Sign up to set email alerts
|

The role of chemokines and chemokine receptors in multiple sclerosis

Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease that is characterized by leukocyte infiltration and subsequent axonal damage, demyelinating inflammation, and formation of sclerosing plaques in brain tissue. The results of various studies in patients indicate that autoimmunity and inflammation make an important impact on the pathogenesis of MS. Chemokines are key mediators of inflammation development and cell migration, mediating various immune cell responses, including chemotaxis and immune activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 128 publications
1
61
0
1
Order By: Relevance
“…Interestingly, it has also been reported that C1P promotes macrophage chemoattractant protein-1 (MCP-1) released in different types of cells, and this chemokine was revealed to be a major mediator of C1P-stimulated cell migration events ( 54 , 55 ). However, C1P-stimulated macrophage migration could be blocked by PA, a glycerophospholipid structurally related to C1P ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has also been reported that C1P promotes macrophage chemoattractant protein-1 (MCP-1) released in different types of cells, and this chemokine was revealed to be a major mediator of C1P-stimulated cell migration events ( 54 , 55 ). However, C1P-stimulated macrophage migration could be blocked by PA, a glycerophospholipid structurally related to C1P ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 demonstrates the recent understanding of the 4 chemokine subfamilies and their receptors (for reviews, please see). [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]…”
Section: Targeting Chemokines and Chemokine Receptors As Immunotherapmentioning
confidence: 99%
“…Chemokines and their receptors are increasingly expressed in MS patients. 30 The chemokines/chemokine receptors axis expressed in T cells have the capability of recruiting inflammatory cells into CNS, which may lead to its destruction. 26,30 Different chemokines play pathogenic roles in MS.…”
Section: Role Of Chemokines In the Pathophysiology Of Msmentioning
confidence: 99%
See 2 more Smart Citations